(untitled) (International Seven Journal of Multidisciplinary, 2023)
The service sector is constantly growing around the world. The quality of services is a differential for organizations to stand out from the competition. Today the market is not only about new technologies and new products, but also about the strengthening and innovations brought to the existing process. The objective of this work is to analyze the processes used by the restaurant L’amitié, to complement the studies carried out on Quality in Services. A case study was carried out at the site, where it was possible to analyze the restaurant’s operation and the services provided. For this analysis, a visit to the restaurant took place, where conversations were held with the owner and the administrator to learn more about the history and the environment. After compiling all the data collected and comparing it with what was learned in theory, it was possible to conclude that the work was carried out in a clear way and reached the objectives proposed in the beginning. DOI: 10.56238/isevmjv2n1-001